DIALECTICS OF SUPREME MOTHER'S RIGHTS IN CARING FOR CHILDREN WHO ARE NOT MUMAYIZ IN CHILDREN RIGHTS DISPUTE IN INDONESIA - M. Nasikhul Umam Al-Mabruri; Syamsul Anwar; Abdul Mustaqim (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This paper examines the custody of the child in which the child is still 1 year and nine months old, while the other case is five years old. This paper is here to analyze cases of child custody through court decisions and also to investigate more deeply the rules. Two things that the writer emphasizes in writing, first, why is the judge granting custody of the child to the father, even though the child is still a minor. Second, how the rules are arranged in classical books, the goal is to know the specific rules in classical books, especially child custody. This study uses a psychology perspective. This paper reveals that the judge has not been so sensitive to the custody of children who are still mumayiz because the judge considers that what the mother does is part of the neglect of the child, even though it is quite clear in the decision regarding the reasons that have been put forward properly so that the mother should have a greater right to care for young children. So that the psychological and mental aspects of the child can be fulfilled even though they are not complete as safety for parents who are still living and raising children together.